Endoscopic sleeve gastroplasty: a potential endoscopic alternative to surgical sleeve gastrectomy for treatment of obesity - Abu Dayyeh, Barham K.; Rajan, Elizabeth; Gostout, Christopher J. (Gastrointestinal endoscopy, 2013)
Obesity and its associated conditions, including type 2 diabetes and cardiovascular disease, have reached epidemic proportions. High-efficacy, high-risk surgical approaches are unlikely to meet the increasing burden of disease. Emerging endoscopic technologies have opened the door for endoscopic approaches to reproduce many of the benefits of GI weight loss surgery and thereby contribute to the effective treatment of obesity and its associated disorders. To demonstrate the technical feasibility of transoral endoscopic gastric volume reduction with an endoscopic suturing device in a fashion similar to sleeve gastrectomy for the treatment of obesity. Single-center, pilot feasibility study. Four human subjects with obesity. Transoral sleeve gastroplasty. Technical feasibility. We successfully used an endoscopic free-hand suturing system in 4 subjects, thus demonstrating the technical feasibility of a novel technique to mimic the anatomic manipulations created by surgical sleeve gastrectomy endoscopically. Pilot feasibility study with small number of subjects. Endoscopic sleeve gastroplasty for treatment of obesity is feasible.